2020
DOI: 10.1101/2020.03.01.971499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kallikrein 13: a new player in coronaviral infections

Abstract: 35Human coronavirus HKU1 (HCoV-HKU1) is associated with respiratory disease and is 36 prevalent worldwide, but in vitro model for virus replication is lacking. Interaction between the 37 coronaviral spike (S) protein and its receptor is the major determinant of virus tissue and host 38 specificity, but virus entry is a complex process requiring a concerted action of multiple cellular 39 elements. Here, we show that KLK13 is required for the infection of the human respiratory 40 epithelium and is sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…Plasmin also cleaves the S proteins of SARS-CoV in vitro (37). In addition, HCoV-HKU1 S proteins are cleaved by kallikrein in the S1/S2 region and mediate the entry of HCoV-HKU1 to nonpermissive rhabdomyosarcoma cells (54). The clinical relevance of non-furin cleavage remains unknown due to the paucity of in vivo evidence for the role of plasmin cleavage of SARS-CoV.…”
Section: B Cleavage Of Coronavirus By Plasmin and Other Host Proteasesmentioning
confidence: 99%
“…Plasmin also cleaves the S proteins of SARS-CoV in vitro (37). In addition, HCoV-HKU1 S proteins are cleaved by kallikrein in the S1/S2 region and mediate the entry of HCoV-HKU1 to nonpermissive rhabdomyosarcoma cells (54). The clinical relevance of non-furin cleavage remains unknown due to the paucity of in vivo evidence for the role of plasmin cleavage of SARS-CoV.…”
Section: B Cleavage Of Coronavirus By Plasmin and Other Host Proteasesmentioning
confidence: 99%
“…While in the first one they enter via pH-dependent endocytic pathway, in 77 the latter one they utilize surface serine proteases as TMPRSS2 or kallikreins for activation and 78 the fusion occurs on the cell surface. This may have grave consequences not only for the basic 79 science, but also the antiviral drug development 12,13,14,20 . 80 Here we verified whether HAE cultures may be used to study the SARS-CoV-2 infection 81 and identified the cellular targets in the tissue.…”
mentioning
confidence: 99%
“…Although the literature surrounding the contact system and coronavirus is limited, there has been recent work about the roles of kallikrein and angiotensin-converting enzyme (ACE). In a preliminary study by Milewska et al, researchers studied the role of kallikrein 13 (KLK13) in HCoV-HKU1, a coronavirus discovered in Hong Kong in 2004 [14]. Human airway epithelial (HAE) cell cultures were incubated with HCoV.…”
Section: The Contact System and Coronavirus Infectionsmentioning
confidence: 99%
“…Based on mRNA expression, human tissue kallikreins (KLK) KLK1, KLK5, KLK6, KLK9, KLK12 and KLK14 were significantly expressed in the infected cells. In particular, HCoV-HKU1 infection was dependent on KLK13 activity, and HCoV-HKU1 did not replicate in HAE cells deficient in KLK13 [14]. Perhaps KLK13 inhibitors could serve as a novel therapy to prevent or treat coronavirus infections.…”
Section: The Contact System and Coronavirus Infectionsmentioning
confidence: 99%
See 1 more Smart Citation